COMPARATIVE ANALYSIS OF PERENNIAL WOOD OF SOME SPECIES OF PLANTS - Akynbek Tajibaev; Zhanylbu Rakhmanovna Berdibaeva (World Science, 2022)
The article presents data from the study of perennial wood of woodyshrub plants in the mountainous regions of the southwestern Tien Shan of Central Asia. It was found that, despite the common opinion about the aridity of the region’s climate, among the studied species, there are a KEYWORDS variety of adaptive characteristics of the studied organ.